Port-Access Thoracoscopic Anatomical Segmentectomy for Pediatric Intralobar Pulmonary Sequestration - Inoue, Takashi; Oizumi, Hiroyuki; Nakamura, Megumi; Sadahiro, Mitsuaki (The Thoracic and Cardiovascular Surgeon Reports, 2014)
This report describes successful port-access thoracoscopic anatomical left lateral and posterior basal (S9 + 10) lung segmentectomy performed for intralobar pulmonary sequestration (ILPS) in a 5-year-old girl with recurrent pneumonia. Computed tomography revealed a multilocular lung abscess and an anomalous artery arising from the left gastric artery supplying the affected segment. After diagnosing ILPS, we performed thoracoscopic anatomical S9 + 10 segmentectomy. We consider thoracoscopic lung segmentectomy to be an important therapeutic option for pediatric ILPS.
Keywords: thoracic surgery; minimally invasive surgery; lung; congenital disorder; pediatric; thoracoscopy/VATS; computed tomography